The Dynamics of the Quality of Life of Tuberculosis Patients in Palembang City: A Phenomenological Study - Fitri Yaldo; Desy Arisandi (Green Publisher Indonesia, 2026)
This study aims to explore the dynamics of the quality of life of tuberculosis (TB) patients in Palembang City through a phenomenological study. Tuberculosis is not merely a physical disease that attacks the respiratory system, but also has a significant impact on the psychological aspects and overall well-being of patients. The high incidence of TB in Palembang City, which records the highest cases in South Sumatra Province, underscores the importance of understanding the perceptions and lived experiences of those affected. The method used in this study is descriptive qualitative with a phenomenological approach. The research subjects consisted of two TB patients with a history of disease relapse (initials AS and F), supported by two knowledgeable informants from the family and Patient Support Group. Data were collected through in-depth interviews and documentation techniques. Data analysis was conducted using the Miles and Huberman model and the Spradley model to draw systematic conclusions. The results of the study indicate that both subjects were able to achieve an adequate level of quality of life despite having to face physical challenges due to treatment side effects and psychosocial burdens in the form of stigma and limited social interaction. The dynamics of a patient's quality of life are significantly influenced by several key factors, including microsystem (family) support, access to government health services, and spiritual strength and internal motivation to recover. Adaptability and effective emotional regulation have been shown to be crucial elements in maintaining well-being throughout long-term treatment.